Pengaruh Arah Serat dan Fraksi Volume terhadap Kekuatan Impact Komposit Serat Tebu (Sugar Cane Fiber) Epoxy - Moch Rakha Naufal Athilah; Widjanarko Widjanarko (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study aims to examine the effect of fiber orientation and volume fraction on the impact strength of sugarcane fiber–epoxy composites. Sugarcane fiber is considered a promising natural reinforcement material due to its lightweight, renewable nature, and environmental friendliness. Specimens were fabricated using the vacuum bagging method with fiber orientations of 0°, 60°, 90°, and random, and volume fractions of 5%, 10%, 15%, and 20%. Impact testing was conducted according to ASTM D6110-10 to determine absorbed energy and impact strength. The results show that both fiber orientation and volume fraction significantly influence impact strength. The highest impact strength was achieved with a 15% volume fraction and 0° fiber orientation, reaching 0.085 J/mm² or an absorbed energy of 8.5 Joules. In contrast, the lowest value was recorded at a 15% volume fraction with 90° fiber orientation, yielding 0.018 J/mm² or 1.8 Joules. The interaction between these variables also contributed significantly to enhancing material toughness. These findings highlight the importance of optimizing fiber orientation and volume fraction in designing natural fiber-based composites for lightweight structural applications